REALIZATION OF APOLOGY STRATEGIES BY ENGLISH DEPARTMENT STUDENTS OF PEKALONGAN UNIVERSITY (Universitas Negeri Semarang, 2012)
This study is meant to find out the apology strategies, to investigate the development strategies from the lowest to the highest semester students, and to explain how the pragmatic transfer interferes the apology strategis used by English Department students of Pekalongan University. This study used a qualitative descriptive design and written discourse completion tasks were employed to obtain the data. As a subject study, ten students were taken from each semester, so there were forty students overall. In analyzing the data, the students’ apologies were analyzed by using Holmes classification. The findings reveal that an explicit expression of apology, in particular, the strategy of expressing regret, is the most frequent apology strategy. Alerter and explanation are also used extensively. There is development of the use of apology strategies from the lowest to the highest semester students. With pragmatic transfer, pragma-linguistic transfer is dominated by linguistic features changing from Indonesian language to English, whereas the socio-pragmatic transfer is more dominated by a socio-culture changing from Indonesian to English, making it unacceptable in English language context.